Irradiation biology of male brown marmorated stink bugs: is there scope for the sterile insect technique?. (2nd December 2017) - Welsh, T. J.; Stringer, L. D.; Caldwell, R.; Carpenter, J. E.; Suckling, D. M.
Abstract: Purpose: Brown marmorated stink bugs, Halyomorpha halys Stål (Hemiptera: Pentatomidae), are regularly intercepted, but there are few eradication tools. Currently, no sterile insect technique program exists for Hemiptera. Materials and methods: Adult males were irradiated at 4–60 Gy, mated and their progeny reared for two generations, with mortality assessed at F 1 egg, F 1 adult and F 2 egg stages. Results: The F 1 eggs showed a dose response to irradiation between 4 and 36 Gy, with 97% sterility at 16 Gy, and higher doses producing complete egg mortality. Only rare F 1 survivors had progeny, but the F 2 generation showed identical responses between maternal and paternal lines; most egg batches showed either very low or very high mortality. Irradiation with 16 Gy resulted in 98.5% sterility, cumulative over F 1 and F 2 . Conclusions: Lack of a dose response at the F 2 generation precludes the use of irradiation-induced inherited sterility. The conventional sterile insect technique appears possible by irradiation of males from ∼12 to 16 Gy. The effect of radiation dose on females is not known, thus we cannot conclude whether bi-sex release is feasible so for now the release of males only is recommended. More work is needed on the competitive fitness of irradiated males, and logistics such as mass rearing or field collection, in order to determine the feasibility of the approach. Graphical Abstract: